Selenium Biofortification Impacts the Nutritive Value, Polyphenolic Content, and Bioactive Constitution of Variable Microgreens Genotypes - Antonio Pannico; Christophe El-Nakhel; Giulia Graziani; Marios C. Kyriacou; Maria Giordano; Georgios A. Soteriou; Armando Zarrelli; Alberto Ritieni; Stefania De Pascale; Youssef Rouphael (MDPI AG, 2020)
Selenium (Se) is considered essential for human nutrition as it is involved in the metabolic pathway of selenoproteins and relevant biological functions. Microgreens, defined as tender immature greens, constitute an emerging functional food characterized by overall higher levels of phytonutrients than their mature counterparts. The nutraceutical value of microgreens can be further improved through Se biofortification, delivering Se-enriched foods and potentially an enhanced content of bioactive compounds. The current study defined the effect of sodium selenate applications at three concentrations (0, 8, and 16 μM Se) on the bioactive compounds and mineral content of coriander, green basil, purple basil, and tatsoi microgreens grown in soilless cultivation. Analytical emphasis was dedicated to the identification and quantification of polyphenols by UHPLC-Q-Orbitrap-HRMS, major carotenoids by HPLC-DAD, and macro micro-minerals by ICP-OES. Twenty-seven phenolic compounds were quantified, of which the most abundant were: Chlorogenic acid and rutin in coriander, caffeic acid hexoside and kaempferol-3-O(caffeoyl) sophoroside-7-O-glucoside in tatsoi, and cichoric acid and rosmarinic acid in both green and purple basil. In coriander and tatsoi microgreens, the application of 16 μM Se increased the total phenols content by 21% and 95%, respectively; moreover, it improved the yield by 44% and 18%, respectively. At the same Se dose, the bioactive value of coriander and tatsoi was enhanced by a significant increase in rutin (33%) and kaempferol-3-O(feruloyl)sophoroside-7-O-glucoside (157%), respectively, compared to the control. In green and purple basil microgreens, the 8 μM Se application enhanced the lutein concentration by 7% and 19%, respectively. The same application rate also increased the overall macroelements content by 35% and total polyphenols concentration by 32% but only in the green cultivar. The latter actually had a tripled chicoric acid content compared to the untreated control. All microgreen genotypes exhibited an increase in the Se content in response to the biofortification treatments, thereby satisfying the recommended daily allowance for Se (RDA-Se) from 20% to 133%. The optimal Se dose that guarantees the effectiveness of Se biofortification and improves the content of bioactive compounds was 16 μM in coriander and tatsoi, and 8 μM in green and purple basil.